2023
DOI: 10.1590/1517-8692202329012023_0050
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Intensity Interval Training on Physical Fitness and Body Composition of Obese College Students

Abstract: Introduction: Maintaining body composition and physical fitness is important for the well-being of college students. Recent data indicate an increase in obesity among young college students and new techniques have been studied to control this situation. Among the current resources is high-intensity interval training. Objective: Explore the effects of high-intensity interval training on physical fitness and body control in obese male college students. Methods: The experimental control involved 100 obese male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Other studies' findings on obese teens revealed a reduction in body fat percentage following moderate-intensity exercise (Buchan et al, 2011). In their study on male obesity among college students, Yuan and Hu (2023) found that a combination of aerobic exercise and high-intensity intermittent strength training can significantly enhance body shape and composition. Cardio exercise, also known as aerobic exercise, is an exercise that requires oxygen to burn energy (Permadi, 2019;Souza et al, 2020).…”
Section: Effect Of Cardio and Tabata Training On Fat Percentagementioning
confidence: 94%
“…Other studies' findings on obese teens revealed a reduction in body fat percentage following moderate-intensity exercise (Buchan et al, 2011). In their study on male obesity among college students, Yuan and Hu (2023) found that a combination of aerobic exercise and high-intensity intermittent strength training can significantly enhance body shape and composition. Cardio exercise, also known as aerobic exercise, is an exercise that requires oxygen to burn energy (Permadi, 2019;Souza et al, 2020).…”
Section: Effect Of Cardio and Tabata Training On Fat Percentagementioning
confidence: 94%